2021
DOI: 10.2166/ws.2021.273
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic performance of riverbank filtration: case study West Sohag, Egypt

Abstract: Riverbank Filtration (RBF) Technology has been found to be a safe, renewable, sustainable, and cost-effective drinking water treatment or pretreatment technology. The Egyptian government has recently turned to riverbank filtration to conserve drinking and industrial water at a lower cost and higher efficiency. The study aims to assess the hydraulic performance of the riverbank filtration system in west Sohag, Egypt. MODFLOW and MODPATH 10.2.3 were used under the platform of Groundwater Modeling System (GMS) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Abd-Elaty et al (2021c) showed that the reduction in the river stages and the aquifer abstraction well rates had lowered the portions of bank filtrate, while the high productivity of RBF wells increased the RBF. Shebl et al (2021) showed that the surface water quality, the aquifer hydraulic characteristics, and the RBF system, including well number, distances, and abstraction rates, influence the RBF sharing. Pholkern et al (2015) and Jaramillo et al ( 2019) evaluated RBF systems using numerical and experimental models to simulate pesticide removal.…”
Section: Discussionmentioning
confidence: 99%
“…Abd-Elaty et al (2021c) showed that the reduction in the river stages and the aquifer abstraction well rates had lowered the portions of bank filtrate, while the high productivity of RBF wells increased the RBF. Shebl et al (2021) showed that the surface water quality, the aquifer hydraulic characteristics, and the RBF system, including well number, distances, and abstraction rates, influence the RBF sharing. Pholkern et al (2015) and Jaramillo et al ( 2019) evaluated RBF systems using numerical and experimental models to simulate pesticide removal.…”
Section: Discussionmentioning
confidence: 99%